2017
DOI: 10.1371/journal.pone.0188231
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of stroke teams and simulation training shortened process times in a regional stroke network—A network-wide prospective trial

Abstract: BackgroundTo meet the requirements imposed by the time-dependency of acute stroke therapies, it is necessary 1) to initiate structural and cultural changes in the breadth of stroke-ready hospitals and 2) to find new ways to train the personnel treating patients with acute stroke. We aimed to implement and validate a composite intervention of a stroke team algorithm and simulation-based stroke team training as an effective quality initiative in our regional interdisciplinary neurovascular network consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 18 publications
0
22
0
1
Order By: Relevance
“…Existing studies rely on one-time interventions at a simulation facility (22), trained hospitals with little prior experience (23) and/or used retrospective case analyses as a comparator (23, 24). We have previously applied the stroke team approach to the sponsor's stroke admissions team (16) and consequently to our regional stroke network (17), which at the time consisted of seven stroke units. In that study, we found that the intervention (algorithm design, introducing CRM, and simulation training) was effective in reducing the network wide door-to-needle time from a median of 43 min (IQR 30–60 min) to 31 min (IQR 24–42 min) (16) and door-to-groin-time from 59 min (IQR 35–102 min) to 43 min (IQR 28–81 min) (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies rely on one-time interventions at a simulation facility (22), trained hospitals with little prior experience (23) and/or used retrospective case analyses as a comparator (23, 24). We have previously applied the stroke team approach to the sponsor's stroke admissions team (16) and consequently to our regional stroke network (17), which at the time consisted of seven stroke units. In that study, we found that the intervention (algorithm design, introducing CRM, and simulation training) was effective in reducing the network wide door-to-needle time from a median of 43 min (IQR 30–60 min) to 31 min (IQR 24–42 min) (16) and door-to-groin-time from 59 min (IQR 35–102 min) to 43 min (IQR 28–81 min) (25).…”
Section: Discussionmentioning
confidence: 99%
“…This intervention was highly efficient (16). We transferred a trimmed-down version of the intervention—relying on a peer-to-peer review of the respective acute stroke algorithms and a one-time simulation training—to our regional stroke network consisting of stroke units of different certification levels where it significantly reduced the network-wide median door-to-needle time in a pre-test-post-test analysis (17).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation is used in this case as an educational technique to ensure prompt attention and assessment. Tahtali et al [50] proposed to train the subjects based on the data collected regarding the care provided to the patient, over conferences given to the health workers and suggested that a well-structured team generally consists of a neurologist, radiologist, resident, and nurse, who Table 2. Advantages of implementing medical simulation in neurovascular care education [46][47][48][49] Advantage of simulation in neurovascular care The "know-how" of the three essential principles of knowledge in medical education is put into practice.…”
Section: Simulation In Neurovascular Critical Carementioning
confidence: 99%
“…A study recently stated that the crucial factors for excellent stroke care are “soft factors” which can be addressed by (a) connecting SPOKE and HUB centers, (b) a well-coordinated team work of various medical and nursing staff (stroke team), and (c) transmission of the relevant knowledge and skills to all personnel involved in acute stroke therapy on a regular basis. 72 In this era of modern stroke therapy, patient safety is not only avoiding adverse events such as bleeding following thrombolysis but also achieving maximal patient benefit by avoiding delays to treatment. The basic elements needed to perform thrombolysis or selecting candidates for mechanical thrombectomy are neither very complex nor expensive.…”
Section: Moving In the Right Direction—how Do We Tackle These Challenges?mentioning
confidence: 99%